Assessment of CD73 activity in breast cancer-derived small extracellular vesicles: application to monitoring of patients’ responses to immunotherapy - T.L. Whiteside; S. Sehra; T. Chadderton; M. Guha; M.C. Stubbs; C. Timmers; E.K. Jackson (Immuno-Oncology and Technology)
Background: We previously discovered that small extracellular vesicles (sEV) isolated from melanoma cells produce immunosuppressive adenosine (ADO) via the ATP→ADP→AMP→ADO pathway and that CD73 is the ‘gateway’ ecto-nucleotidase used by melanoma sEV to generate ADO. Here we extend these findings to CD39(+)CD73(+) and CD39(+)CD73(−) sEV from breast cancer cells. Materials and methods: sEV were isolated from supernatants of a triple-negative breast cancer cell line ± the genetic knockout of CD73. A newly developed high pressure liquid chromatography assay with fluorescence detection was used for assessment of N6-etheno-AMP conversion to N6-etheno-ADO by sEV. PSB12379 (selective CD73 inhibitor) and anti-CD73 antibodies were used to inhibit/neutralize CD73 activity in sEV. Results: Untreated sEV isolated from CD39(+)CD73(+) breast cancer cells readily metabolized N6-etheno-AMP to N6-etheno-ADO, and this activity was abolished by PSB12379. sEV from CD39(+)CD73(−) breast cancer cells were unable to metabolize N6-etheno-AMP to N6-etheno-ADO. Effects of three different anti-CD73 antibodies on CD73 activity in sEV were examined. Only one antibody, the direct binding pocket inhibitor of CD73, but not antibodies that allosterically inhibit recombinant CD73, attenuated conversion of N6-etheno-AMP to N6-etheno-ADO by cancer-derived sEV. Conclusions: In breast cancer-derived sEV, as in melanoma-derived sEV, CD73 is the gateway enzyme regulating ADO formation from upstream AMP. The quantitation in sEV of N6-etheno-AMP conversion to N6-etheno-ADO ± neutralizing anti-CD73 antibodies provides a measure of the ability of these antibodies to suppress ADO production and could potentially serve as a personalized predictor of CD73 activity in patients with cancer.